Epidemics of Abundance: Overeating and Slimming in the USA and Britain since the 1950s. - Offer, A (Nuffield College (University of Oxford), 1998)
Body weight has risen in defiance of health and appearance norms. The social epidemics of overeating and slimming were driven by market forces and the psychology of eating: restrained eating is easily disinhibited by stress. For men, the rise in body weight was associated with the decline of family eating and exposure to greater food variety. For women, the ‘cult of slimming’ was associated with mating competition, driven initially by adverse sex ratios. Food abundance made a mockery of the rational consumer. Paradoxically, the costs of abundance fell more heavily on the poor, who have had less access to the resources of self-control.